EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN SAVI TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP NEGERI 4 PADANGSIDIMPUAN - Deli Sari Siregar (JURNAL MathEdu (Mathematic Education Journal), 2018)
This study aims to describe effectiveness of using SAVI learning model on students’ mathematical communication ability on the topic lines and angles on the topic at the seventh grade students of SMP Negeri 4 Padangsiidmpuan. The research was conducted by using descriptive method with 30 students as the sample and they were taken by using random sampling technique from 174 students. Test and observation were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using SAVI learning model on was 3.67 (very good category), b) the average of students’ mathematical communication ability on the topic lines and angles before using SAVI learning model was 44.66 (poor category) and after using SAVI learning model was 71.2 (good category), and c) the describe of effectiveness of using SAVI learning model on students’ mathematical communication ability on the topic lines and angles was 1) 6.7% students gave answer enough category, 2) 76.7% students gave answer good category, and 3) 16.7% students gave answer very good category.